Dissolution kinetics of Indian PHWR natural UO2 fuel pellets in nitric acid – Effect of initial acidity and temperature. (August 2015) - Desigan, N.; Augustine, Elizabeth; Murali, Remya; Pandey, N.K.; Kamachi Mudali, U.; Natarajan, R.; Joshi, J.B.
Abstract: Understanding the dissolution behaviour of plutonium rich MOX fuel is one of the major challenges in fast reactor spent fuel reprocessing. As an initial step, kinetics for the dissolution of Indian PHWR natural UO2 sintered pellets in nitric acid was studied experimentally. In this paper we have reported the effect of initial nitric acid concentration and temperature on dissolution rate of sintered UO2 pellets. The shrinking core model was used to correlate the experimental results. The apparent activation energy estimated from the temperature effect of the chemical reaction was found to be about 90.5 kJ/mol. The estimated apparent activation energy indicates that the dissolution rate of UO2 pellets was controlled by chemical reaction under the experimental conditions. Graphical abstract: Highlights: Dissolution kinetics of Indian PHWR sintered UO2 pellets in nitric acid has been determined. Effect of initial nitric acid concentration has been evaluated quantitatively. The influence of temperature on the reaction rate has been quantified. A shrinking core thermodynamic model has been developed for dissolution. The model was experimentally evaluated and was found satisfactory.